p21 produces a bioactive secretome that places stressed cells under immunosurveillance - Sturmlechner, Ines; Zhang, Cheng; Sine, Chance C.; van Deursen, Erik-Jan; Jeganathan, Karthik B.; Hamada, Naomi; Grasic, Jan; Friedman, David; Stutchman, Jeremy T.; Can, Ismail; Hamada, Masakazu; Lim, Do Young; et al. (Science (American Association for the Advancement of Science), 2021)
Senescent cells promote their own recognition and removal through the immune system by generating a bioactive secretome called the senescence-associated secretory phenotype (SASP). Sturmlechner et al . report that the cell cycle regulator p21 directs an early form of the SASP, which they call the p21-activated secretory phenotype (PASP) (see the Perspective by Reen and Gil). As part of the PASP, the chemokine CXCL14 attracts macrophages, which monitor stressed cells expressing elevated p21. If stressed cells recuperate and p21 levels return to normal within 4 days, then macrophages disengage from their targets. Otherwise, macrophages recruit cytotoxic T cells that facilitate target cell removal. Other cell cycle regulators such as p16 can induce many factors overlapping with the PASP, but p21 uniquely drives this CXCL14-mediated “timer” mechanism of senescent cell immunosurveillance. —STS The cell cycle factor p21 concurrently induces proliferative arrest and immunosurveillance of cells under stress, controlling their fate. Immune cells identify and destroy damaged cells to prevent them from causing cancer or other pathologies by mechanisms that remain poorly understood. Here, we report that the cell-cycle inhibitor p21 places cells under immunosurveillance to establish a biological timer mechanism that controls cell fate. p21 activates retinoblastoma protein (Rb)–dependent transcription at select gene promoters to generate a complex bioactive secretome, termed p21-activated secretory phenotype (PASP). The PASP includes the chemokine CXCL14, which promptly attracts macrophages. These macrophages disengage if cells normalize p21 within 4 days, but if p21 induction persists, they polarize toward an M1 phenotype and lymphocytes mount a cytotoxic T cell response to eliminate target cells, including preneoplastic cells. Thus, p21 concurrently induces proliferative arrest and immunosurveillance of cells under duress.